2023
DOI: 10.1093/bjc/azac100
|View full text |Cite
|
Sign up to set email alerts
|

A Disproportionate Risk of Being Executed: Why Pakistani Migrants Are Vulnerable to Capital Punishment in Saudi Arabia

Abstract: Many labour migrants in the Arab Gulf countries are from South Asia. Necessary to local economies, they enjoy few rights and protections from host states, particularly when accused of serious crimes. Our original empirical data suggests a disproportionate number of Pakistanis sentenced to death and executed in Saudi Arabia and we explore explanations within a wider discussion of the place and experiences of South Asian migrants in the Gulf. Our data suggest that drug laws and penal policies leave migrant worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We found that of the 664 cases in the Gulf, at least 317 foreign nationals were executed during this time and at least 290 are thought to remain on death row. Our data suggest a disproportionate use of the death penalty against migrant workers in Saudi Arabia (Hoyle et al, 2023), the UAE (for drug offences) and Bahrain (for homicide offences). Up to 79% of individuals sentenced to death for drug offences in Saudi Arabia are migrants, and ‘a foreign worker is at least three times more likely to be executed for drug crime than a Saudi’ (Larasati and Girelli, 2021:45).…”
Section: Mapping Migrant Workers On Death Row In the Gulfmentioning
confidence: 72%
See 1 more Smart Citation
“…We found that of the 664 cases in the Gulf, at least 317 foreign nationals were executed during this time and at least 290 are thought to remain on death row. Our data suggest a disproportionate use of the death penalty against migrant workers in Saudi Arabia (Hoyle et al, 2023), the UAE (for drug offences) and Bahrain (for homicide offences). Up to 79% of individuals sentenced to death for drug offences in Saudi Arabia are migrants, and ‘a foreign worker is at least three times more likely to be executed for drug crime than a Saudi’ (Larasati and Girelli, 2021:45).…”
Section: Mapping Migrant Workers On Death Row In the Gulfmentioning
confidence: 72%
“…Oman and Yemen were excluded as there was a dearth of reliable data, though both countries receive migrant workers and apply the death penalty. As Table 2 shows, most are from South and Southeast Asia, with a considerable, and disproportionate, number of Pakistani nationals sentenced to death for drug offences (Hoyle et al, 2023).…”
Section: Mapping Migrant Workers On Death Row In the Gulfmentioning
confidence: 99%
“…Even when the death penalty is prominently used against drug offenders-as in Southeast Asia-ordinary criminal justice and political symbolism often overlap, for example when drugs trafficking is constructed as a threat to national security and the moral order and the death penalty is used disproportionally against foreigners, who are turned into the new "other" and are scapegoated for social ills (Harry, 2023). 18 Indeed, the overlap between ordinary law enforcement and political symbolism in the contemporary death penalty is indicated by the growing targeting of non-nationals in death penalty laws and practices (Hoyle, 2019;Hoyle et al, 2023). A few illustrations: in 2015, of 14 people executed in Indonesia, just two were Indonesian nationals; in 2013 five men were hanged in Kuwait, none of whom were Kuwaiti nationals; 82% of death row inmates in the UAE are foreign nationals (Hoyle, 2019); in Saudi Arabia, one of the world's highest executing states, 43% of executions are of foreign nationals (Hoyle et al, 2023).…”
Section: Dudaimentioning
confidence: 99%
“…18 Indeed, the overlap between ordinary law enforcement and political symbolism in the contemporary death penalty is indicated by the growing targeting of non-nationals in death penalty laws and practices (Hoyle, 2019;Hoyle et al, 2023). A few illustrations: in 2015, of 14 people executed in Indonesia, just two were Indonesian nationals; in 2013 five men were hanged in Kuwait, none of whom were Kuwaiti nationals; 82% of death row inmates in the UAE are foreign nationals (Hoyle, 2019); in Saudi Arabia, one of the world's highest executing states, 43% of executions are of foreign nationals (Hoyle et al, 2023). This is partly a result of discriminatory practices, but also because "foreigners" are considered as a threat to national security and identity (Hoyle, 2019).…”
Section: Dudaimentioning
confidence: 99%
See 1 more Smart Citation